Pengembangan Bahan Ajar Kimia Berbasis Lahan Basah Berbantuan Liveworksheet Bagi Guru Kimia Kabupaten Barito Kuala - Parham Saadi; Rusmansyah; Hestu Anggrah Eny; Ade Rahmawati Idris; Gusti Aulia Nasution; Melda Sapitri; Sandrina Eka Avrillianti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
The Merdeka Curriculum demands learning innovations that are contextual, interactive, and relevant to 21st-century skills, namely the 6C Skills (Critical Thinking, Collaboration, Communication, Creativity, Citizenship, and Character). This activity is a community service program that embodies the tridharma of higher education, led by a team of lecturers majoring in chemistry and their students. The activity was conducted in the form of training on the development of wetland-based chemistry teaching materials for the SCCrT model, assisted by Liveworksheet, which was carried out in collaboration with MGMP Kimia of Barito Kuala Regency. The goal is to enhance the competence of chemistry teachers in designing innovative teaching materials that foster critical thinking, collaboration, communication, creativity, citizenship, and character development in students. The implementation method includes planning, implementation, evaluation, and reflection. The results of this service activity indicate an increase in the skills of chemistry teachers in developing innovative teaching materials for the wetland-based SCCrT model. Chemistry teachers are also able to utilise the Liveworksheet platform in the development of chemistry learning with the SCCrT model.